Dimensi Kepercayaan dalam Usaha Pelepas Uang (Studi Kasus di Kabupaten Semarang) - Yustinus Wahyudi; Gatot Sasongko (Institut Teknologi Sepuluh Nopember, 2019)
The informality of the money lender business is closely related to transaction costs and risks in carrying out its business. Trust is vital and plays an important role in the sustainability of money lender businesses. Trust serves to reduce transaction costs, mortgage loan risks and the determination of collateral. This study will look at the role of trust dimensions, namely ability, benevolence, and integrity in money lender loan transactions in Semarang Regency. To achieve this goal, the research uses a qualitative approach with case studies, which aims to comprehensively understand the role of the dimensions of trust in lending transactions in money lender businesses. As a result, every dimension of trust plays a role in money lender loan transactions.